PENGARUH ASSURANCE SUSTAINABILITY REPORT TERHADAP MARKET VALUE PERUSAHAAN YANG TERDAFTAR DI BEI PADA TAHUN 2011-2013 - Hanif Rahmansyah; Faisal Faisal (Diponegoro Journal of Accounting, 2015)
Currently Indonesian companies began to publish sustainability report as a corporate responsibility to the environment. To increase the credibility of the sustainability report, the company did assurance, but not much research the topic of assurance. This study aimed to analyze the effect of assurance on the sustainability report to the market value of the company. This study used independent assurance, size, leverage, ROA, the type of industry to measure the market value of the company.This study used secondary data documentation, they were sustainability report and annual report companies that listed on the Stock Exchange in 2011-2013. The sampling method used in this research is purposive sampling with some requirements. The number of samples obtained from these criteria were 36 companies with a total of 108 samples. in This study used multiple linear regression to test the hypothesis.The results showed that the assurance negative and not significant effect to the market value of the company. Other variables such as the size (the size of the company), leverage, and the type of industry also did not have a significant effect. Only ROA which had a positive and significant effect to the market value of the company.